Atmosfera controlada em tomate pitenza - Campos, André José de; Vieites, Rogério Lopes [UNESP]; Neves, Leandro Camargo; Robles, Pedro Antonio; Garcia, Antonio Asencio Calderon (My University, 2013)
This study aimed to evaluate the effect of controlled atmosphere (CA) in the conservation of tomatoes 'Pitenza', by the evaluation of chemical variables, bioactives and enzymatic. The fruits were harvested in the region of Cartagena - Spain and, immediately after harvest, transported to the laboratory, where they were maintained at 12 ± 1 ° C for 21 days. The fruits were subjected to the following treatments: Air (control: 21%O2: 0,03%CO2), CA1 (5%O2:5%CO2) e CA2 (5%O2:1%CO2). The evaluations were conducted as the ascorbic acid content, polyphenols, antioxidant capacity, lycopene, carotenoids and lipoxygenase. Under the conditions in which the experiment was conducted, the results showed that the fruits control, not subjected to AC, showed the better maintenance of 'Pitenza' tomatoes quality during the experimental period.

O presente trabalho teve por objetivo avaliar o efeito da atmosfera controlada (AC) na conservação de tomates „Pitenza‟, pela avaliação de variáveis química, bioativas e enzimática. Os frutos foram colhidos na região de Cartagena – Espanha e, imediatamente após a colheita, transportados ao Laboratório, onde foram mantidos a 12 ± 1ºC por 21 dias. Os frutos foram submetidos aos seguintes tratamentos: Ar (controle: 21%O2: 0,03%CO2), AC1 (5%O2:5%CO2) e AC2 (5%O2:1%CO2). Avaliou-se o teor de ácido ascórbico, polifenois, capacidade antioxidante, licopeno, carotenóides e lipoxigenase. Os resultados permitiram concluir que os frutos controle, não submetidos a AC, apresentaram a melhor manutenção da qualidade dos tomates „Pitenza‟ durante o período experimental.
Controlled atmosphere in pitenza tomatoes
Keywords: Solanum lycopersicum; Antioxidants; Bioactive; Lipoxygenase; Solanum lycopersicum; Antioxidantes; Bioativos; Lipoxigenase